Juridical Review of Children as Perpetrators of Violence Resulting in Serious Injury (A Case Study of Court Decision Number 08/Pid.Sus/2015/PN.Dpu) - Afifah; Sri Hartini; Ady Purwoto (JURNAL MAHASISWA YUSTISI, 2026)
This research aims to analyze criminal responsibility and judicial considerations in the case of a child perpetrator of violence causing serious injury, based on Court Decision Number 08/Pid.Sus/2015/PN.Dpu. The study applies a normative juridical method with a qualitative approach, examining secondary data such as legal statutes, legal doctrines, and court verdicts. The findings reveal that although all elements of the crime were proven legally, the implementation of diversion, as part of the restorative justice mechanism in the juvenile criminal justice system, was unsuccessful. The panel of judges still considered non-legal aspects such as the child's age, psychological condition, and social reports from the Correctional Center in delivering the sentence. The sanctions imposed, including imprisonment and work training, reflect an emphasis on the child's rehabilitation and protection. This study highlights the need for technical guidelines and a more substantive implementation of diversion practices.